Relationship of Family Support to the Referral Program for Patients with Chronic Diseases in BPJS Health Participants in Rawasari Health Center - Andi Subandi; Dwi Noerjoedianto; Andy Amir (Budapest International Research and Critics University, 2021)
Chronic diseases in Indonesia during the current JKN can be handled with the Referral Program (PRB). As one of the flagship programs of BPJS Health to improve the quality of health services for BPJS Health participants and facilitate access to health services for participants with chronic diseases. DRR has not run optimally, 34.05% of the 1.18 million participants with a diagnosis of referral back in Indonesia are implementing DRR. The percentage of active DRR participants at the Rawasari Health Center in 2020 in January-June decreased from 60.06% to 46.32%, in July increased to 49.8% and in September decreased to 47.09%. Family support is very much needed, so that the goal of DRR to reduce the cost of health services in FKTL is achieved. This study aims to determine the relationship between family support and PRB for patients with chronic disease who are BPJS Health participants at the Rawasari Health Center in 2021. This study is a quantitative study using cross sectional. The population is chronic disease BPJS Health participants who actively participate in DRR at Rawasari Health Center as many as 495 people with a total sample of 92 respondents. The sampling technique used was accidental sampling. Data were analyzed by univariate and bivariate using chi square. Bivariate analysis of Chi Square test found that there was no relationship between emotional support (p=0.190) and assessment support (p=0.130). Meanwhile, there is a relationship between instrumental support (p=0.043) and informational support (p=0.001). Variables related to instrumental and informational support. Variables that are not related to emotional support and assessment. Family support is needed to increase the activity of DRR participants.